(untitled) (LACCEI, 2024)
This research arises from the increasingly urgent need to have accessible water sources to improve the quality of life of the majority of rural populations in the high Andean areas where surface and subsurface water sources are scarce In this sense, the use of fog catcher systemwas proposed as an option to water shortages, especially in these high Andean rural areas where there is apparent fog and fog to generate water in a liquid state. The objective of the research was to compare the efficiency of the volume of water captured using three types of fog catching meshes for local climatic conditions in the 22 de Mayo Populated Center, located in the heights of the Peruvian Andes at an altitude of 3296 m.a.s.l., measurements were made daily from September 2021 to March 2022, For the study, 3 two-dimensional fog catchers were used in which the volume of water captured daily was measured to correlate with the meteorological information obtained with a semi-automatic station installed in situ. The methodology used is of the IDPD type (identify, describe, deepen and disseminate) According to the results obtained , there is evidence of a better efficiency of capture of the fog catcher with surgical fabric mesh, noting that both the fog catcher with fique rib mesh as well as the one built with RaSchel type mesh capture on average 50.06% and 25.48% less than Lo capturedby the fog catcher built with surgical fabric mesh respectively.